Identification and analysis of brown planthopper-responsive microRNAs in resistant and susceptible rice plants - Yan Wu (Nature Portfolio, 2017)
Abstract The brown planthopper (BPH) is the most devastating insect pest of rice. The rice gene BPH15 confers resistance to BPH. MicroRNAs (miRNAs) regulate a spectrum of development and defense response processes in plants. In this study, we analyzed six miRNA profiles of a BPH15 introgression line (P15) and a susceptible recipient line (PC) at three time points (0 h, 6 h and 48 h) after BPH attack, and identified 464 known miRNAs and 183 potential novel miRNAs. Before the BPH feeding, we identified 23 miRNAs differentially expressed in P15 and PC. We speculated that the resistant plant is in a priming state by the regulation of miRNAs. After the BPH feeding, 104 miRNAs were found to be expressed differentially in P15 (68 in P15-6/P15-0, 36 in P15-48/P15-0), and 80 miRNAs were found expressed differentially in PC (32 in PC-6/PC-0, 48 in PC-48/PC-0), which illustrated that miRNA expression is activated upon attack. These miRNAs regulate different pathways that contribute to the basal defense and specific resistance of rice to the BPH. Our study provides additional data for scientists to further explore the mechanism of plant defense against insect attack and to find a way for efficient insect control.